FAKTOR-FAKTOR YANG MEMPENGARUHI KEMANDIRIAN SISWA DALAM PEMBELAJARAN BLENDED LEARNING - Deby Andrila; Susi Fitria Dewi; Syafri Anwar; Maria Montessori (Universitas Muria Kudus, 2022)
The purpose of this study is to analyze the factors that influence student learning independence during the blended learning process. The research method used is qualitative. The research data is in the form of statements or spoken words from people and observed behavior into a description of the factors that influence student learning independence in blended learning. The results of the study found that the factors that influence student learning problems in blended learning learning are (1) motivation, low student motivation results in them not being confident in answering the questions given, students trust their friends more than their own answers (2 ) Goals, students who do not have goals in learning will tend to be lazy in learning because they have no goals in the lesson, if students have goals then they will be enthusiastic about learning, because they understand very well the knowledge they will get during the learning process and (3) Parents' attention, students who rarely get attention from their parents, are more likely to be unenthusiastic in learning, not disciplined in learning and irresponsible in learning.